Astrocyte Pannexin 1 Suppresses LPS-Induced Inflammatory Responses to Protect Neuronal SH-SY5Y Cells - Ling, Zhuo-Min; Wang, Qian; Ma, Yu; Xue, Peng; Gu, Yun; Cao, Mao-Hong; Wei, Zhong-Ya (Frontiers in Cellular Neuroscience, 2021)
Reactive astrogliosis is a key hallmark of inflammatory responses in the pathogenesis of brain injury, including Parkinson’s disease (PD), but its role and regulatory mechanisms are not fully understood. Pannexin 1 (Panx 1) is a membrane channel that mediates substance release in many neurodegenerative diseases. However, the role of astrocyte Panx 1 in the regulation of PD-like neuroinflammation remains elusive. Here, we characterized the expression of Panx 1 in isolated primary astrocytes and a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD model. The functions of Panx 1 in inflammatory cytokines expression and the viability of neuronal SH-SY5Y cells were examined in cultured cells treated with lipopolysaccharide (LPS) and 1-methyl-4-phenylpyridinium (MPP+). We found that Panx 1 expression was significantly increased under both LPS- and MPP+-treated conditions. Panx 1 downregulation suppressed LPS-induced pro-inflammatory cytokine expression but did not significantly affect MPP+-induced astrocyte apoptosis or inflammatory cytokine expression through treatment with the Panx 1 inhibitor carbenoxolone (CBX) and Panx 1 siRNA. Moreover, silencing Panx 1 in reactive astrocytes had a potentially protective effect on the viability of neuronal SH-SY5Y cells. Therefore, we propose that Panx 1 may serve as a key regulator in reactive astrocytes to intervene in the inflammatory response and maintain neuronal viability in the context of PD-like conditions.